A dialética espacial da modernização da mandiocultura em Sergipe e a subordinação do campesinato - Souza, Ítala Santana (2019)
The notion of space production makes us consider the various levels of reality as different moments of the general reproduction of society in its complexity. We consider then the subject of action: the state, like that of political domination; capital, with its strategies whose purpose is their continued reproduction; the social subjects that in their needs and desires linked to the realization of life human beings, have space as a condition, medium and product of their action. The investigation on the mandioculture space in Sergipe, which we conducted through this Thesis, explains the spatial dynamics of this productive activity, in the context of productive capital restructuring in the countryside, which implied technical changes and the formation of Local Productive Arrangements (LPAs) of flour houses in the state. Such dynamics demanded the elucidation of how the process of globalization of capital drives changes in Sergipe's agrarian space, as well as the relationship between capital and state and all its territorial developments. Based on the dialectical method, we started from a literature review about the production of space in capitalism, the metamorphoses of the relationship between man and nature in the different moments of reproduction. Emphasis was given to the debate on changes to the flexible accumulation regime, when the form of capitalist expansion points to a process of political-administrative decentralization focused on endogenous development, denouncing the nature of the neoliberal policy embraced in correspondence with the new moment of geographical mobility of capital. Through field surveys conducted in the municipality of Lagarto, the largest producer of cassava and manioc flour in the state, in the municipality of Campo do Brito and in the municipality of São Domingos, it was found that despite the expansion of forms of utilization of cassava and Given the potential for added value and the marketing of by-products raised in recent years, almost all cassava production is sold in natura to a third party. The farmer loses control of the production and marketing of the most important final product, which is flour. A relationship of estrangement is established between the subject of production and the product of labor, but above all, a reduction in the producer's income. In this scenario, reality has shown that the mandioculture space, traditionally dominated by the Brazilian peasantry, is being taken over by a process of monopolization of production by agents with greater economic power. The local productive arrangement policy linked to the flour houses intensified the division of the peasant income, transformed the peasant into an employee in his own land or in the flour houses, expanded the feminine and child labor, naturalizing the latter as help. The propagated discourse generates an understanding of the inevitable character of this so-called modernization, neglecting the nature of this rural development model that denies peasants the possibility of self-managing the product of their work. A reality that denotes the need for the organization of the peasantry as a class, which must struggle to reproduce itself far from the domain of capital.________________________________________________________________________________________________________________________________